PENERAPAN METODE SHORTEST ROUTE PROBLEM UNTUK MENENTUKAN RUTE DISTRIBUSI PRODUK GAS LPG 3 KG DENGAN KRITERIA MINIMASI BIAYA TRANSPORTASI DI PT.WWW - Inna Kholidasari; Aurelia Putri Zein; Susanti Sundari (Fakultas Teknik Universitas Tulang Bawang Lampung, 2022)
PT. WWW strives to deliver products in a timely and cost efficient manner. The determination of the LPG distribution route that has been carried out so far is the result of an estimate without calculation so that transportation costs always increase unexpectedly, so PT. WWW cannot determine fixed costs for transportation and time of goods to arrive so that it has an impact on customer satisfaction. The purpose of this study is to determine the path that provides the shortest route so as to minimize transportation costs and as a reference for product distribution and at the same time can answer the problem of the right delivery time and have an impact on customer satisfaction. The results of the study resulted in a better and optimal proposed route where the shortest route for fleet one was through the PAS – ND – LH – BD – PT. WWW with the calculation of the distance: 3.1 + 1.4 + 0.60 + 0.03 totaling 5.13 km / day. And for the fleet two through the PAS – ED – SN – WR – PT. WWW with the calculation of the distance: 3.9 + 2.9 + 1.4 + 4.0 totaling 12.2 km/day. The transportation cost for the six bases is Rp. 1,323,520,-/month